Edukasi Hemat Energi Menuju Sekolah Ramah Lingkungan bagi Guru MI Tarbiyatul Falah Bantar Gebang Bekasi - Singgi Fadly; Dianing Novita Nurmala Putri; Tyas Kartika Sari; Chairul Gagarin Irianto; Widia Sari (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity aims to improve teachers’ understanding of clean energy concepts and energy-saving behavior to support the development of environmentally friendly schools. The activity was conducted at MI Tarbiyatul Falah Bantar Gebang involving teachers as participants. The methods used included counseling, interactive discussions, technology diffusion, and evaluation through pretest, posttest, and questionnaires. The results showed an increase in participants’ understanding, indicated by the improvement of the average score from 62 in the pretest to 86 in the posttest. In addition, questionnaire results showed positive responses with an average satisfaction level of 69.5% in the very good category. This activity has a positive impact on improving energy literacy and teachers’ awareness of the importance of efficient energy use in the school environment.